2015
DOI: 10.1519/jsc.0000000000000954
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Load Intensity on Postexercise Hypotension and Heart Rate Variability after a Strength Training Session

Abstract: The purpose of this study was to compare blood pressure and heart rate variability (HRV) responses in trained men after strength training (ST) sessions with loads of 60, 70, and 80% of a 1 repetition maximum (1RM). Eleven men (age: 26.1 ± 3.6 years; body mass: 74.1 ± 8.1 kg; height: 172.0 ± 4.0 cm; body mass index: 25.0 ± 1.96 kg·m(-2); %G: 18.3 ± 6.4) with at least 6-month ST experience participated in this study. After assessment of 1RM loads for the bench press (BP), lat pull-down (LPD), shoulder press (SP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 15 publications
3
52
1
8
Order By: Relevance
“…Após executarem o protocolo de exercício programado para o seu grupo, foram novamente postos sentados em repouso absoluto, e enfim, tiveram sua PA aferida durante 60 minutos, em ciclos de 10 minutos (Figueiredo et al, 2015). A PA foi aferida sempre no braço direito, com o manguito posicionado 2 centímetros acima da fossa antecubital, com o indivíduo sentado, costas apoiadas, braços e pernas descruzados.…”
Section: Pressão Arterial E Variabilidade Da Frequência Cardíacaunclassified
See 2 more Smart Citations
“…Após executarem o protocolo de exercício programado para o seu grupo, foram novamente postos sentados em repouso absoluto, e enfim, tiveram sua PA aferida durante 60 minutos, em ciclos de 10 minutos (Figueiredo et al, 2015). A PA foi aferida sempre no braço direito, com o manguito posicionado 2 centímetros acima da fossa antecubital, com o indivíduo sentado, costas apoiadas, braços e pernas descruzados.…”
Section: Pressão Arterial E Variabilidade Da Frequência Cardíacaunclassified
“…Os dados foram registrados após 15 minutos de repouso absoluto durante dez e sessenta minutos pré e pós-exercício respectivamente estando o indivíduo sentado, com pontos de corte de 10 em 10 minutos para efeito de análise (Figueiredo et al, 2015). Uma rotina previamente elaborada no software Matlab (version 6.0, Mathworks, Massachusetts, USA) foi utilizada para análise dos dados no domínio da freqüência.…”
Section: Pressão Arterial E Variabilidade Da Frequência Cardíacaunclassified
See 1 more Smart Citation
“…Rio-Rodriguez et al (12) analyzed the acute effect of two methods in resistance training (clustering and multi-sets) on HRV in moderately trained individuals and demonstrated that HRV reduced in both conditions, although the multi-sets method revealed significantly greater attenuation. In the same direction, Figueiredo et al (13) reported a decrease in HRV after performing resistance training sessions (60, 70 and 80% of 1RM), adopting the multi-sets method. It is worth mentioning again that the respective studies evaluated the acute effect of resistance training on HRV.…”
Section: Discussionmentioning
confidence: 86%
“…Although studies have indicated that resistance training performed with an intensity greater than 60% of 1RM causes autonomic nervous system disturbance, representing on the reduction of HRV (12,13), the scientific literature pointed out that exposure to repeated stimuli (aerobic exercise), as long as there is balance between stress and recovery, can lead to an increase in HRV (3,7). According to Peçanha et al (1), the increase in HRV can be explained by the optimization of the activation of the parasympathetic band and reduction of the sympathetic tone, which is explained by the reduction in plasma concentration of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%